Delirium Monitoring in the ICU: Strategies for Initiating and Sustaining Screening Efforts - Pun, Brenda T.; Devlin, John W. (Seminars in Respiratory and Critical Care Medicine, 2013)
Delirium in the intensive care unit (ICU) is associated with many negative outcomes, including increased length of stay in both the ICU and the hospital, increased duration of mechanical ventilation, increased mortality, worse long-term cognitive impairment, and increased costs. The 2013 American College of Critical Care Medicine (ACCM)/Society of Critical Care Medicine (SCCM) clinical practice guidelines for pain, agitation, and delirium (PAD), based on available evidence, strongly recommend that critically ill patients be routinely monitored for delirium in the ICU using a validated tool. After conducting a thorough psychometric review of available delirium assessment tools, the 2013 PAD guideline group concluded that the Confusion Assessment Method for the ICU (CAM-ICU) and the Intensive Care Delirium Screening Checklist (ICDSC) are the ICU delirium screening tools with the strongest validity and reliability. This article discusses the importance and feasibility of delirium screening in the ICU and compares the most commonly used critical care delirium screening instruments. Strategies needed to implement and sustain delirium screening efforts in different critically ill populations are introduced and discussed. Accurate detection is the first step in managing ICU patients who develop delirium in an attempt to reduce the negative sequelae of delirium in this population.
Keywords: delirium; assessment; implementation; critical care; intensive care unit; education; recognition; CAM-ICU; ICDSC